Estratégias retóricas no discurso de José Sarney - Cândido, Ismael Silva (2011)
This research aims to analyze the rhetorical strategies used by the Senator Jose Sarney during the presentation of his candidacy to the chair of the Federal Senate. The theoretical basis are the Aristotle’s lessons in his work called The Art of Rhetoric and the Art of Poetry, as well as the studies of Perelman and Tyteca (2005), according to which "the rhetoric is the art of arguing." For Perelman and Tyteca (2005), rhetoric is the study of discursive techniques that allow to promote or to increase the adherence of the spirits to the thesis that are presented for assent. Thus, our goal is to show the power of rhetoric and argumentation as a factor in the power perpetuation. We want to show how the words when well used can direct the course of a listener and even a whole audience. Regardless of political-party ideology, we intend to show how the "art of well speaking” is a major factor for those who, provided with good or bad faith, use the word as their modification tool of society. To attain our goal, we employ several studies on the rhetoric and argumentation, especially Aristotle (2005), Citelli (2007), Osakabe (2002), Mosca (2004), Orlandi (1999), Reboul (2004), Tringali ( 1988), Perelman and Tyteca (2005). The methodology of this research consists of a close reading of the José Sarney’s discourse, delivered at the session of the Federal Senate in which was presented the register of his candidacy for president of that House and the analysis of the rhetorical devices used by him.